Educação a distância na formação de professores: o curso-piloto "Consumo Sustentável/Consumo Responsável - desenvolvimento, cidadania e meio ambiente. - Shimizu, Rita de Cassia Gromoni (Universidade Federal de São Carlos, 2006)
The present research analysed the results of the distance pilot-course Consumo Sustentável/Consumo Responsável - desenvolvimento, cidadania e meio ambiente , that it was proposed by CECEMCA, through the accord between MEC and UNESP, approved in 2004 and offered to teachers in a public elementary school in the Rio Claro city. The methodology consisted on analyzing three questionnaires, the homeworks, the observed class and the narrative, besides another questionary developed to answering the following question: How the Basic Education´s teachers evaluated their participation on the distance pilot-course Consumo Sustentável/Consumo Responsável - desenvolvimento, cidadania e meio ambiente ? In a review of literature it were searched works about Distance Environmental Education, but it were not found papers that focused Sustainable Consume. The results proved that it is necessary to reformulate some aspects to the next courses. However, in the teachers´ point of view, the course contributed to their teaching practice and professional development.
Keywords: Professores - formação; Ensino a distância; Educação ambiental; Distance education; Environmental education; Teacher education; CIENCIAS HUMANAS::EDUCACAO